All-cellulose-based quasi-solid-state supercapacitor with nitrogen and boron dual-doped carbon electrodes exhibiting high energy density and excellent cyclic stability - Kaixuan Li; Ping Li; Zining Sun; Jing Shi; Minghua Huang; Jingwei Chen; Shuai Liu; Zhicheng Shi; Huanlei Wang (Green Energy & Environment, 2023)
The key to construct high-energy supercapacitors is to maximize the capacitance of electrode and the voltage of the device. Realizing this purpose by utilizing sustainable and low-cost resources is still a big challenge. Herein, N, B co-doped carbon nanosheets are obtained through the proposed dual-template assisted approach by using methyl cellulose as the precursor. Due to the synergistic effects form the high surface area with the hierarchical porous structure, N/B dual doping, and a high degree of graphitization, the resultant carbon electrode exhibits a high capacitance of 572 F g−1 at 0.5 A g−1 and retains 281 F g−1 at 50 A g−1 in an acidic electrolyte. Furthermore, the symmetric device assembled using bacterial cellulose-based gel polymer electrolyte can deliver high energy density of 43 W h kg−1 and excellent cyclability with 97.8% capacity retention after 20 000 cycles in “water in salt” electrolyte. This work successfully realizes the fabrication of high-performance all-cellulose-based quasi-solid-state supercapacitors, which brings a cost-effective insight into jointly designing electrodes and electrolytes for supporting highly efficient energy storage.